2007
DOI: 10.1529/biophysj.107.105007
|View full text |Cite
|
Sign up to set email alerts
|

Force-Response Considerations in Ciliary Mechanosensation

Abstract: Considerable experimental evidence indicates that the primary, nonmotile cilium is a mechanosensory organelle in several epithelial cell types. As the relationship between cellular responses and nature and magnitude of applied forces is not well understood, we have investigated the effects of exposure of monolayers of renal collecting duct chief cells to orbital shaking and quantified the forces incident on cilia. An exposure of 24 h of these cells to orbital shaking resulted in a decrease of amiloride-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 21 publications
2
75
0
Order By: Relevance
“…34 While these load induced alterations in gene expression in tendon cells cannot be directly attributed to a mechanosensory function of the primary cilium, the affects of loading have been associated with changes in cilia length. 9,18,21,31,32 Tensile loading of rat tail tendons has been shown to result in fluid flow, 25,26 and cellular deformations. 24 Both of these mechanisms have previously been associated with a decrease in cilia length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 While these load induced alterations in gene expression in tendon cells cannot be directly attributed to a mechanosensory function of the primary cilium, the affects of loading have been associated with changes in cilia length. 9,18,21,31,32 Tensile loading of rat tail tendons has been shown to result in fluid flow, 25,26 and cellular deformations. 24 Both of these mechanisms have previously been associated with a decrease in cilia length.…”
Section: Discussionmentioning
confidence: 99%
“…24 Both of these mechanisms have previously been associated with a decrease in cilia length. Fluid flow has been shown to decrease cilia lengths in renal cells 18,21,31,32 and loss of primary cilia from the endothelial surface of human umbilical cord cells. 19 Conversely, cyclic cellular deformation via compression loading of chondrocyte-agarose constructs significantly decreased lengthened cilia in free-swelling constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated a possible need to regulate the length of primary cilia in response to extracellular environmental changes. For instance, kidney cells can adjust the length of cilia in reaction to fluid stimuli; a deficiency in the regulation of the length and shape causes some disorders, termed ciliary diseases (14,21). Moreover, the primary cilium functions as a chemoreceptor which perceives the extracellular environment via membrane-bound receptors and ion channels expressed on cilia (23).…”
mentioning
confidence: 99%
“…Algebraically: 1N ϭ 1(kg ‫ء‬ m)/s 2 Thus, a typical cell could exert up to 1,047 ϫ 10 -15 N on its primary cilium due to the relative positions of the Earth, Sun, and Moon, depending on the orientation of the cell in the gravitational field with respect to its primary cilium. Interestingly, a single primary cilium is capable of detecting a shear force of 5.2 ϫ 10 -15 N (Resnick and Hopfer, 2007). This suggests that the primary cilium is sensitive enough to detect the cyclic change in Earth's gravitational field.…”
Section: Rohon Beard Neuron Primary Ciliamentioning
confidence: 99%